Selected ancient stone bridges with corbelled false-arch structure = Wybrane starożytne mosty kamienne z łukami o konstrukcji opartej na łęku pozornym - Maślak, Mariusz; Partov, Doncho (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The oldest man-made false-arch stone bridges are presented and briefly described. It is shown that this construction technique was based on the experiences of the first builders, formed at the junction of ancient Egyptian, Mycenaean as well as Assyrian and Babylonian cultures.
Keywords: arch stone bridge; false arch; needle vaule; mud brick arch; corbelled arch; culvert; aqueduct; most kamienny łukowy; łuk fałszywy; sklepienie igłowe; łuk z cegły mułowej; łęk pozorny; przepust; akwedukt